EVALUATING L2 VOCABULARY DEVELOPMENT FEATURES USING LEXICAL DENSITY AND LEXICAL DIVERSITY MEASURES - Abu-Rabiah, Eihab (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Most of the research on lexical measures was conducted in English and conducted similarly in other languages without accurate adaptations to the language being tested. The first objective of this study is to identify differences between applications of lexical density and lexical diversity when tested as in English and when adapted to the language being tested. The second objective is to inspect the effect of acquisition time on intermediate-level second-language learners' lexical density and diversity. In a test-retest study over one year, Arabic Hebrew bilinguals (n=23) wrote argumentative essays, in which lexical density and diversity were analyzed according to two approaches; a conventional approach as in English and an adapted approach more aligned with Hebrew linguistic features. In both approaches, lexical density was calculated as the number of lexical words in proportion to the total number of words and lexical diversity using the type-token ratio (TTR) and Corrected TTR (CTTR). Findings reveal statistically significant differences between the two approaches and the adapted approach allowed for cross-language and interlanguage comparisons. Although no significant increase in lexical density and diversity over the year was found, various patterns for lexical development were observed; at the second time point, students with the lowest level of lexical diversity substantially improved and more essays fell within the lexical density range of a typically written language.